2014
DOI: 10.1111/1348-0421.12127
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐hepatitis C virus compounds obtained from Glycyrrhiza uralensis and other Glycyrrhiza species

Abstract: Development of complementary and/or alternative drugs for treatment of hepatitis C virus (HCV) infection is still much needed from clinical and economic points of view. Antiviral substances obtained from medicinal plants are potentially good targets to study. Glycyrrhiza uralensis and G. glabra have been commonly used in both traditional and modern medicine. In this study, extracts of G. uralensis roots and their components were examined for anti-HCV activity using an HCV cell culture system. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 40 publications
0
100
0
Order By: Relevance
“…Many previous studies have demonstrated its variety of biological functions, such as anti-inflammatory [27], anti-oxidative [26], chemopreventive activities [29], and anti-platelet aggregation properties [28], and so on. Also, ISL has been reported to suppress replication of HCV in a dose-dependent manner [35]. IFN-γ/JAKs/ STAT1 pathway is the classical pathway to regulate IFN-inducible genes expression, and several studies showed that the expression of CXCL9-10 was induced via the activation of JAK1, JAK2/STAT1 [36].…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have demonstrated its variety of biological functions, such as anti-inflammatory [27], anti-oxidative [26], chemopreventive activities [29], and anti-platelet aggregation properties [28], and so on. Also, ISL has been reported to suppress replication of HCV in a dose-dependent manner [35]. IFN-γ/JAKs/ STAT1 pathway is the classical pathway to regulate IFN-inducible genes expression, and several studies showed that the expression of CXCL9-10 was induced via the activation of JAK1, JAK2/STAT1 [36].…”
Section: Discussionmentioning
confidence: 99%
“…We tested ethanol extracts of Indonesia plants for their anti-HCV activities and reported that Toona sureni leaves, Melicope latifolia leaves, Melanolepis multiglandulosa stem and Ficus fistulosa leaves possessed anti-HCV activities [10]. We also reported that extracts of Glycyrrhiza uralensis root and isolated compounds, such as glycycoumarin, glycerin, glycyrol, and liquiritigenin, and extracts of Morinda citrifolia leaves, an isolated compound, pheophorbide a, and its related compound, pyropheophorbide a, exhibited anti-HCV activities [11,12]. Likewise, silymarin, iridoid, epigallocatechin-3-gallate were reported to inhibit HCV infection at the entry step while diosgenin, luteolin, quercetin, 3-hydroxy caruilignan C, excoecariphenol D and apigenin at the post-entry step [13,14].…”
Section: Introductionmentioning
confidence: 94%
“…Time-of-addition experiments were performed to assess the mode of action of the samples, as described previously [10][11][12]. In brief, three sets of experiments were done in parallel.…”
Section: Analysis Of Anti-hcv Activitiesmentioning
confidence: 99%
“…It was reported also that pyropheophorbide A is an anti-HCV compound with IC 50 value of 0.2 µg/ml [10]. Adianti et al suggested that glycycoumarin, glycerin, glycerol, and liquiritigenin isolated from Glycyrrhiza uralensis, as well as isoliquiritigenin, licochalcone A, and glabridin, would be good candidates for seed compounds to develop antivirals against HCV [11]. Quercetin and gallic acid isolated from Kalanchoe pinnata inhibited HCV production in a dose-dependent manner with IC 50 value of 1.5 and 6.1 µg/ml, respectively, without exhibiting cytotoxicity [12].…”
Section: Introductionmentioning
confidence: 99%